INDUSTRIAL DEVELOPMENT OF UZBEK SPECIALTY PRODUCTS ON CHINESE E-COMMERCE PLATFORMS BACKGROUND, SECTOR OVERVIEW, AND HISTORICAL SIGNIFICANCE (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Uzbekistan's specialty products, such as Suzani embroidery, ceramics, silk, and dried fruits, possess significant cultural advantages, but their entry into the Chinese e-commerce market is limited by weak branding, insufficient standardization, and a lack of digital capabilities. This study, combining global value chains and e-commerce platform mechanisms, assesses their suitability for the Chinese e-commerce market through literature, case studies, and platform analysis.
Keywords: Specialty Products; SMEs in Export-oriented Industries; Cross-border E-commerce Platforms; China–Uzbekistan Industrial Cooperation; Belt and Road Initiative (BRI).